Hubungan antara Self-Disclosure dan Social Skills dengan Quality Friendship Siswa SMAN se-Kecamatan Slawi - Della Aprilya Rara Imelsiana; Najma Sana Nadhirah Hilman Nadhirah Hilman (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Friendship quality is an important aspect of adolescent social development because it supports emotional security, peer acceptance, identity formation, and psychological well-being. During adolescence, students increasingly rely on peer relationships, making interpersonal competencies such as self-disclosure and social skills relevant factors in understanding the quality of their friendships. This study aimed to examine the relationship between self-disclosure and social skills with quality friendship among senior high school students in Slawi District. A quantitative correlational design was employed using multiple linear regression analysis. The participants consisted of 286 tenth-grade students from three public senior high schools in Slawi District selected through cluster sampling. Data were collected using three Likert-scale instruments measuring self-disclosure, social skills, and quality friendship. The quality friendship instrument was adapted from Farida and Tjiptorini based on Bukowski’s theory, the social skills instrument was adapted from Kusumaningsih based on Gresham and Elliott’s theory, and the self-disclosure instrument was adapted from Kinanti based on Altman and Taylor’s theory. The data were analyzed using SPSS version 26 after the assumptions of normality, linearity, multicollinearity, heteroscedasticity, and residual independence were fulfilled. The results showed that self-disclosure and social skills were simultaneously and significantly related to quality friendship, F(2, 283) = 19.605, p < 0.001. The adjusted coefficient of determination was 0.115, indicating that both variables explained 11.5% of the variance in quality friendship. Partially, self-disclosure was not significantly related to quality friendship, β = 0.033, t = 0.590, p = 0.556, whereas social skills were positively and significantly related to quality friendship, β = 0.344, t = 6.126, p < 0.001. These findings indicate that students’ social skills play a more prominent role than self-disclosure in explaining friendship quality. This study provides practical implications for school counselors in developing guidance and counseling programs that strengthen students’ social skills, interpersonal communication, empathy, cooperation, and conflict resolution to promote healthier and more supportive peer relationships.